Normothermic regional perfusion in liver transplantation from donation after cardiocirculatory death: Technical, biochemical, and regulatory aspects and review of literature. Issue 9 (22nd June 2022) - Melandro, Fabio; Basta, Giuseppina; Torri, Francesco; Biancofiore, Giandomenico; Del Turco, Serena; Orlando, Francesco; Guarracino, Fabio; Maremmani, Paolo; Lazzeri, Chiara; Peris, Adriano; De Simone, Paolo; Ghinolfi, Davide
Abstract: Background: Organs from donation after circulatory death (DCD) are increasingly used for liver transplantation, due to the persisting organ shortage and waiting list mortality. However, the use of DCD grafts is still limited by the inferior graft survival rate and the increased risk of primary non‐function and biliary complications when compared to brain death donors' grafts. Methods: Abdominal normothermic regional perfusion with extracorporeal membrane oxygenation (ECMO) is an in situ preservation strategy. which may mitigate ischemia–reperfusion injuries. and has been proposed to restore blood perfusion after the determination of death thus optimizing liver function before implantation. Results: In this systematic review, we highlighted the clinical evidence supporting the use of normothermic regional perfusion in DCD liver underlying the pathophysiological mechanisms, and technical, logistic, and regulatory aspects. Conclusions: Despite the lack of properly designed, prospective, randomized trials, the current available data suggest beneficial effects of normothermic regional perfusion on clinical outcomes after liver transplantation. Abstract : This review aims to investigate the biological principles, the technical aspects, the viability criteria and the results of the use of normothermic regional perfusion in DCD liver transplantation. NRP is an in‐situ preservation strategy which may mitigate ischemia‐reperfusion injuries and reduce the complications after Liver Transplantation. Despite the lack of properly designed, prospective, randomized trials, the currently available data suggest beneficial effects of NRP on clinical outcomes after liver transplantation.